PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 003 TASIK JUANG KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Nafsiyah, Nafsiyah; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is in the science learning value of student learning outcomes very rendahmasi bannyak child who likes to talk with sebangkunya, do not want to do the assignment of teachers, students do not want to answer a question that is given by the teacher and did not want to ask if it does not understand , Very obvious from the problems of the students, how the learning outcomes of their students. As a result, students can not absorb the lessons well. Based on these problems it is necessary to find a way to solve those problems.. Subjects in this study were students of class IV Elementary School 003 Lake Juang academic year 2014/2015 the number of students 22 people. The research was conducted in the second cycle of each II meetings in the first cycle as well as in the second cycle and the second time the end of Deuteronomy. Instrument collecting data in this study is the observation sheet rublik teachers and students as well as teacher and student activity assessment tests daily test cycle I and II. This research was conducted with the form of classroom action research (PTK), aims to improve the results bejajar Elementary School fourth grade students 003 Lake Juang in science lessons. These results indicate bashwa Quantum models Teachingdapat improve learning outcomes IPA. This can be seen from the Improvement of learning outcomes of prior to the implementation of the model Quantum Teaching is 56.40 from 22 people who follow replicates only 6 complete and 16 incomplete with persentase72,8% with less category. At UH I Cycle I hariansiswa value increased to 70.68 sebanyak65% who have increased the number of students who tuntas12 people. In the second cycle increased the average value of as much as 26.9% to 76.59. Students who complete mencapai18 people. Class can be declared complete when reaching 70 of the number of students who reach the specified KKM is 70. It can be concluded that Quantum Teaching learning model can improve learning outcomes IPA Elementary School fourth grade students 003 Lake District of Lubuk Batu Juang Jaya.Key word. Quantum teaching, outcomes IPA